Redes organizacionais: perspectiva para a sustentabilidade de uma ONG em Uberlândia-MG - Sousa, Edileusa Godói de (2005)
The third sector is going through a period of changes due to growing social problems, reduction of public investments in the social area, growth of the organizations in this sector, and companies investment in social actions. Hence, there is an increase in uncertainty and insecurity of the organizations in this sector, which need to adapt, restructure, become more flexible, and permanently search for ways to innovate according to the new configurations of the environment. Thus, non-governmental organizations are facing the challenge of having to continuously think about their relationships with other organizations of the same sector, with State organizations, and with companies in order to increase the synergy between one and the other and to deepen the reciprocity of these relations. Therefore, the term "organizational networks" gains ground, offering opportunities for partnership as a means of sustainability of third-sector organizations. The discussion of this work is placed in the former context. The aim was to investigate the feasibility of inter-sector and inter-organizational networks aspiring a sustainability perspective for non-governmental organizations. At first, ponderings over the third-sector were made emphasizing non-governmental organizations. Secondly, a conceptual basis was constructed to bring back the concepts and definitions of sustainability and organizational networks. Finally, a case study of the NGO "LAR de Amparo e Promoção Humana" in the town of Uberlândia MG was presented. This institution was chosen due to its projection in the number of people assisted, the variety of sectors that assisted these people and for adopting a management based in organizational networks regarding not only its sustainability but also its expansion, which is linked to the purpose of this analysis. The analysis categories that conducted the empirical study were guided by the following: economic sustainability, social sustainability and cultural sustainability, as well as the forms, the nature of the relationship between the partners, and the sorts of connections in the organizational networks. Applied methodological procedures were used instead of experimental ones. The predominant approach was qualitative, more specifically, descriptive qualitative. Semi-structured interview techniques, direct observation and document analysis were used for gathering data. The triangulation technique was used for data analysis and interpretation. The research results show that the gathering and availability of resources from organizational networks are a permanent challenge for the organization studied. As far as this study suggests, when there is a set of norms, rules and procedures pre-established by the partners, the meeting, which should be based on cooperation, ends up being a meeting for providing services. However, we are led to believe that those organizations which achieve a greater proximity especially to the Public Power, supplying part of the Government s demand by offering quality assistances, have a higher sustainability perspective for having access to fundamental resources in implementing its social projects. In spite of that, in the following development of these actions, there are still possibly many challenges for the organization, especially related to finding and sustaining the articulate bonds of a variety of relationships.